Analyze The Effect of Communication, Teamwork, And Work Environment on Employee Loyalty and Employee Performance of Pt Peputra Pekanbaru - Nicholas Renaldo; Kelvin Wijaya; Eveline Tanshia; , Achmad Tavip Junaedi; Nyoto Nyoto (PT. Keberlanjutan Strategis Indonesia, 2026)
Purpose:This research aims to analyze the influence of communication, teamwork and work environment on the loyalty and performance of PT Peputra Pekanbaru employees.Methodology:This research is qualitative research. Data was collected through questionnaires from employees at the company. The population in this study was all 34 employees. The sampling technique uses the purposive method. The types of data sources are primary data and secondary data, while the data collection techniques are observation and questionnaires. The data processing method uses multiple regression analysis with the t test, F test, and R square as a statistical research method using SPSS.Findings:The results of this research show that communication and teamwork have a positive and significant effect on employee performance, while the work environment does not have a significant effect on employee performance.